The Effect of Radiotherapy on Oxidative Stress, Biochemical and Hematological Parameters inWomen with Breast Cancer - Rouia A. R. Abulkassim; Dawsar K. Ismael; Nawfal A. M. Numan; Nada N. Al-Shawi; Saad A. R. Hussain (College of Pharmacy / Mustansiriyah University, 2014)
This study was designed to evaluate the effect of radiation therapy on the oxidative stress, biochemical and hematological parameters in women with breast cancer. 95 women were studied, 20 healthy control women and 75 had breast cancer. Malondialdehyde and glutathione (in erythrocytes and plasma), biochemical parameters (total plasma proteins, plasma albumin, uric acid and plasma calcium) levels, and hematological parameters (hemoglobin, white blood cell counts, platelets counts) all parameters were measured pre- and post radiation therapy for 4 weeks. The result of this study indicates that the incorporation of radiation therapy as a way to destroy malignant cells, in addition to their therapeutic benefits, it may lead to further increase in the oxidative stress burden of cancer, manifested by increase in MDA production and glutathione depletion. Which may affect directly or indirectly some biochemical and hematological parameters as indicated by lowering plasma protein especially albumin, increases in plasma calcium level, and decreases in hemoglobin, white blood cells, and platelets levels. These changes should be considered during radiation therapy and before administration of anticancer drugs or any other drugs because it may affect both the beneficial as well as the toxicity of these drugs.